Next generation microbiome applications for crop production — limitations and the need of knowledge-based solutions. (June 2019) - Mitter, Birgit; Brader, Günter; Pfaffenbichler, Nikolaus; Sessitsch, Angela
Abstract : Plants are associated with highly diverse microbiota, which are crucial partners for their host carrying out important functions. Essentially, they are involved in nutrient supply, pathogen antagonism and protection of their host against different types of stress. The potential of microbial inoculants has been demonstrated in numerous studies, primarily under greenhouse conditions. However, field application, for example, as biofertilizer or biocontrol agent, is still a challenge as the applied microorganisms often are not provided in sufficiently high cell numbers, are rapidly outcompeted and cannot establish or require specific conditions to mediate the desired effects. We still have limited understanding on the fate of inoculants and on holobiont interactions, that is, interactions between plants, micro-biota and macro-biota and the environment, under field conditions. A better understanding will provide the basis for establishing models predicting the behaviour of strains or consortia and will help identifying microbiome members being able to establish and to mediate desired effects under certain conditions. Such models may also inform about the best management practices modulating microbiota in a desired way. Also, smart delivery approaches of microbial inoculants as well as the selection or breeding of plant genotypes better able to interact with microbiota may represent promising avenues.